HAMBATAN STARTUP EDUKASI SETELAH PROGRAM INKUBASI (STUDI KASUS PADA PROGRAM INKUBATOR STARTUP CIAS) - Rasyid Nata Mulyana; Oktapiana Aula; Djogi Banyu Adem; Asep Nuryadin; Adi Prehanto (Jurnal Ilmiah Manajemen "E M O R", 2022)
ABSTRACT Startups as solutions to various problems in Indonesia are now starting to get the spotlight because they are starting to see the contribution and real impact of startups in providing improvements in various areas. But of the many companies that develop startups in Indonesia, only a few are able to survive and succeed in generating profits. Therefore, this research was conducted with the aim of knowing the factors or obstacles for a startup to be able to develop. This study uses a qualitative approach with case study methods and data collection techniques using questionnaires and interviews with the aim of digging up detailed information. Questionnaires and interviews were distributed to educational startups that had completed the CIAS incubator program, namely Learning Hours, Learning and Chit Chat Apps startups. Based on the research results, there are findings that all startups that have survived so far must have experienced obstacles. Various kinds of obstacles were found in this study, including difficulties in finding investors, inadequate human resources, and lack of funds to carry out business development. The results of this study are expected to be a valuable reference, especially for incubators and startup actors in developing their startups in the future. Keyword: Startup, Hambatan, CIAS, Bisnis, Inkubator ABSTRAK Startup sebagai solusi dari berbagai permasalahan di Indonesia kini mulai mendapatkan sorotan karena mulai terlihat kontribusi serta dampak nyata startup dalam memberikan perbaikan di berbagai bidang. Oleh karena itu penelitian ini dilakukan dengan tujuan untuk mengetahui faktor atau hambatan sebuah startup untuk dapat berkembang. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus dan teknik pengambilan data menggunakan angket dan wawancara yang bertujuan menggali informasi secara rinci. Penyebaran angket dan wawancara dilakukan pada startup pendidikan yang telah selesai menjalani program inkubator CIAS yaitu startup Jam Belajar, Lapak Belajar, dan Chit Chat Apps. Berdasarkan hasil penelitian, terdapat temuan bahwa semua startup yang bertahan selama ini pasti pernah mengalami hambatan. Berbagai macam hambatan yang ditemukan dalam penelitian ini diantaranya kesulitan dalam mencari investor, sumber daya manusia yang kurang tepat, dan kekurangan dana untuk melakukan pengembangan bisnis. Hasil penelitian ini diharapkan dapat menjadi rujukan berharga terutama untuk inkubator dan pelaku startup dalam mengembangan startupnya di masa depan. Keyword: Startup, Barriers, CIAS, Business, Incubator